ANIOŁ U NORWIDA - Waksmundzka, Iwona (Colloquia Litteraria, 2019)
Angel in Norwid’s oeuvre The author explores the angel motif in Cyprian Norwid’s body of work. The article opens with a definition of ‘angel’ as a term and an exposition of selected works of angelology, philosophy, and philology which deal with this motif/being in thought, culture, and literaturę. The author primarily deals with literary works from the nineteenth century; she quotes multiple examples from Norwid’s writings pointing to the intensity and importance of the presence of the angel in his oeuvre. The main part of this study ana- lyses the character and function of the angel in Ostatnia z bajek.